FINANCIAL INCENTIVES TO EXPORTING SMEs IN EMERGING MARKETS. - de Souza, Izabel; Floriani, Dinora Eliete; Borini, Felipe Mendes (Revista de Negócios, 2016)
The purpose is to analyze whether use of government incentives by exporting SMEs in Brazil helps them increase their degree of internationalization (DOI) and/or improve their export performance. The regression model reveals that greater use of financial incentives was related to higher DOI and better performance. However, the variable percentage of sales financed had a negative influence on DOI, on export performance and on international competitiveness, showing that the lower the percentage financed, the higher the DOI.